PERILAKU MENCOBA BELI: SEBUAH KAJIAN ANALITIS MODEL BAGOZZI-WARSHAW UNTUK PANDUAN PENELITI - Basu Swastha Dharmmesta (Faculty of Economics and Business, Universitas Gadjah Mada, 2000)
Theory of reasoned action (Ajzen and Fishbein, 1980) and its’ further development, called theory of planned behaviour (Ajzen, 1987), according to Bagozzi dan Warshaw (1990), need to be reviewed in more detail especially on the behavioural aspect. The later theory emphasises more on behaviour of trying (trying to act something, such as trying to purchase or trying to use), instead of the behaviour itself. Trying is perceived as a more appropriate criterion for an individual who intend to try. Position of other variables does not relatively change as shown by those, other than its’ behavioural aspect, in the theory of planned behaviour. Predictive power of the model is estimated to be higher than the previous two models.